2020
DOI: 10.47149/pemo.v2i2.3747
|View full text |Cite
|
Sign up to set email alerts
|

A possibilidade de utilização do blog como ferramenta educacional

Abstract: O presente artigo tem o objetivo de discutir como o uso das Tecnologias Digitais de Informação e Comunicação – TDIC –, tendo como foco o blog, favorece o processo educativo de ensino. A pesquisa qualitativa aliou revisão bibliográfica e aplicação de um questionário aos alunos do curso de Pedagogia da Universidade Estadual do Ceará, para evidenciar os seguintes enfoques: o conhecimento do aluno acerca do blog, o uso do blog na vida acadêmica, a percepção avaliativa do blog no contexto educacional e a utilização… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…In a study conducted by Vieira, Belo, and Freire (2020) with students in the initial years of the Pedagogy course, it was found that the majority of these students have some knowledge about blogs; however, their experience with this tool in the educational context is limited or even non-existent. Moreover, for those who had some exposure, the use of this tool catered to individual interests without the guidance of an educator (Vieira, Belo & Freire, 2020). Based on this, it's understood that the inclusion of DICT in teachers' knowledge is necessary so that various technological tools, such as blogs, can be integrated into the daily classroom routine.…”
Section: Nevermentioning
confidence: 99%
“…In a study conducted by Vieira, Belo, and Freire (2020) with students in the initial years of the Pedagogy course, it was found that the majority of these students have some knowledge about blogs; however, their experience with this tool in the educational context is limited or even non-existent. Moreover, for those who had some exposure, the use of this tool catered to individual interests without the guidance of an educator (Vieira, Belo & Freire, 2020). Based on this, it's understood that the inclusion of DICT in teachers' knowledge is necessary so that various technological tools, such as blogs, can be integrated into the daily classroom routine.…”
Section: Nevermentioning
confidence: 99%